Genetic variability of the horse (Equus caballus) using coat genes in Sahagún, Córdoba, Colombia - Moreno, Cristian (2018)
The aim of this study was to estimate the genetic variability of domestic Creole horses (Equus caballus) through genes associated with the coat. Samples were taken through rural excursions between November 2016 and November 2017 in seven populations in Sahagun, Cordoba. Adult horses present in the farms of each population were sampled, where each animal was phenotypically characterized according to the autosomal markers of morphological coding: Extension, Agouti, Cream, Gray, White, Tobiano, Overo, and Roan. Genetic parameters: allele frequencies, genetic diversity and genetic distance were calculated through the program PopGene 1.31; population structure was determined by the program FSTAT v.2.9.3.2. and the dendrogram was done using the program Mega 7. The results indicated no presence for the White and Overo markers while Extension marker was the most representative in frequency possibly helped by artificial selection. Tobiano marker was the least frequent, which might be related to selection against individuals carrying this marker. Populations were found in Hardy-Weinberg equilibrium, as they showed an excess of heterozygotes and high values of genetic flow between them.